2010
DOI: 10.1111/j.1582-4934.2009.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Human liver stem cell‐derived microvesicles accelerate hepatic regeneration in hepatectomized rats

Abstract: Several studies indicate that adult stem cells may improve the recovery from acute tissue injury. It has been suggested that they may contribute to tissue regeneration by the release of paracrine factors promoting proliferation of tissue resident cells. However, the factors involved remain unknown. In the present study we found that microvesicles (MVs) derived from human liver stem cells (HLSC) induced in vitro proliferation and apoptosis resistance of human and rat hepatocytes. These effects required internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
255
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 274 publications
(262 citation statements)
references
References 45 publications
6
255
0
1
Order By: Relevance
“…In addition, HLSC are known to be positive for several embryonic factors, including nanog, Oct-4, Sox2 and SSEA-4. 21 However, at variance of embryonic stem cells, HLSC are not pluripotent and do not form teratoma, but they are only multipotent as they differentiate in hepatocytes, osteocytes, adipocytes, endothelial and islet-like cells under specific culture conditions. 18 In the present study, we found that the CM of HLSC inhibited proliferation and enhanced apoptosis of HepG2 in vitro and induced HepG2 tumor regression in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, HLSC are known to be positive for several embryonic factors, including nanog, Oct-4, Sox2 and SSEA-4. 21 However, at variance of embryonic stem cells, HLSC are not pluripotent and do not form teratoma, but they are only multipotent as they differentiate in hepatocytes, osteocytes, adipocytes, endothelial and islet-like cells under specific culture conditions. 18 In the present study, we found that the CM of HLSC inhibited proliferation and enhanced apoptosis of HepG2 in vitro and induced HepG2 tumor regression in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…(Cambrex Bio Science, Verviers, Belgium) cultured in minimum essential medium/endothelial cell basal medium-1 (a-MEM/EBM) (3:1) (Cambrex Bio Science) supplemented with L-glutamine (5 mM), Hepes (12 mM, pH 7.4), penicillin (50 IU/ml), streptomycin (50 mg/ml) (all from Sigma-Aldrich, St Louis, MO, USA), fetal bovine serum (FBS, 10%) as previously described. 18,21 The expanded cells were transferred to a T-75 flask and analyzed when they approached confluence.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations